1980
DOI: 10.1107/s056774088000859x
|View full text |Cite
|
Sign up to set email alerts
|

Crystallographic and conformational studies on histamine H1 receptor antagonists. I. Structure of carbinoxamine maleate

Abstract: Carbinoxamine maleate, CI6H20CIN20 +. C4H304, crystallizes in space group P21212~ with a = 10.527 (3), b = 11.151 (3), c = 17.626 (4) A andZ= 4. Diffractometer data were collected with Cu Kct radiation and the structure was refined to an R value of 0.045 using 1448 observed reflections. The compound crystallizes with spontaneous resolution of the enantiomers and the absolute configuration of carbinoxamine was determined to be S in the crystal under investigation. The crystal is built by ion pairs linked by an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1986
1986
2013
2013

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…However reports of carbinoxamine and other antihistamines being harmless to psychomotor performance and driving skills have been shown (Seppala et al, 1981). A study on carbinoxamine maleate describing the crystallographic structure and chemical relationships of Clistin to other well known antihistaminic drugs and also correlating these chemical aspects with the pharmacological effects produced by this new drug as compared with other antihistaminic agents has been reported by Bertolasi et al (1980). Some number of related structures was reported earlier -orphenadrinium picrate picric acid (Fun et al, 2010); orphenadrinium dihydrogen citrate (Kaur et al, 2013); doxylamine hydrogen succinate (Parvez et al, 2001).…”
Section: Methodsmentioning
confidence: 97%
See 1 more Smart Citation
“…However reports of carbinoxamine and other antihistamines being harmless to psychomotor performance and driving skills have been shown (Seppala et al, 1981). A study on carbinoxamine maleate describing the crystallographic structure and chemical relationships of Clistin to other well known antihistaminic drugs and also correlating these chemical aspects with the pharmacological effects produced by this new drug as compared with other antihistaminic agents has been reported by Bertolasi et al (1980). Some number of related structures was reported earlier -orphenadrinium picrate picric acid (Fun et al, 2010); orphenadrinium dihydrogen citrate (Kaur et al, 2013); doxylamine hydrogen succinate (Parvez et al, 2001).…”
Section: Methodsmentioning
confidence: 97%
“…For the effect of antihistamines on psychomotor performance, see: Seppala et al (1981). For related structures, see: Bertolasi et al (1980); Parvez et al (2001); Fun et al (2010); Kaur et al (2013). For standard bond lengths, see: Allen et al (1987).…”
Section: Related Literaturementioning
confidence: 99%
“…For background to pyrimidine compounds, see: Glidewell et al (2003); Panneerselvam et al (2004). For details of maleic acid, see: James & Williams (1974); Bertolasi et al (1980). For hydrogen-bond motifs, see: Bernstein et al (1995).…”
Section: Related Literaturementioning
confidence: 99%
“…A study of the structural chemistry of maleic acid and related substances arises from the fact that these systems possess short but highly strained hydrogen bonds (James & Williams, 1974). The crystal structures of maleic acid (James & Williams, 1974) and carbinoxamine maleate (Bertolasi et al, 1980) have been reported in the literature. We (Bernstein et al, 1995) ring and results in a folded conformation.…”
Section: Crystal Datamentioning
confidence: 99%